Does Employment Protection Reduce the Demand for Unskilled Labor? - Kirsten Daniel; William Stanley Siebert (Institute for the Study of Labor (IZA), 2004)
Perhaps it does. We propose a model in which workers with little education or in the tails of the age distribution – the inexperienced and the old – have more chance of job failure (mismatch). Recruits? average education should then increase and the standard deviation of starting age decrease when strict employment protection raises hiring and firing costs. We test the model using annual distributions of recruits? characteristics from a 1975-95 panel of plants in Belgium, the Netherlands, Italy, the UK and the US. The model?s predictions are supported using the Blanchard-Wolfers index of employment protection as well as our alternative index.
Keywords: J83; J21; 330; employment protection; labor demand; unskilled workers; firm panel data; Kündigungsschutz; Ungelernte Arbeitskräfte; Arbeitsnachfrage; Schätzung; Belgien; Niederlande; Italien; Grossbritannien; Vereinigte Staaten